Arsiparis dalam era digital: analisis bibliografi tentang perkembangan arsiparis dalam database internasional menggunakan vosviewer - Jalinur, Jalinur (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2024)
This research analyzes the trends in archival research from 1939 to the present. The study aims to determine: (1) the development of the number of international publications on archiving in the Scopus database from 1939 to 2023; (2) journals in international publications about archivists; (3) the productivity of the authors; (4) the number of publications based on institutional collaboration in international publications about archivists; (5) the development of international publications on archivist research by subject/field; (6) the mapping of the development of international publications on archivist research based on co-occurrence. Data collection methods involved searching the Scopus database with the keyword "Archivist" using boolean OR, AND, and AND NOT, the period of 1939-2023. Data mapping was conducted using Microsoft Excel and VosViewer software. The results show the highest number of documents in 2022. The research subjects are dominated by social sciences, with the most productive author being R.J. Cox. The country with the most publications is the United States. The keyword mapping of publications reveals nine clusters. Three clusters are closely related, encompassing business environment challenges risk, cloud storage, records, archival service, online marketplace, classification, and text image documents, which might become hot topics in future research.